16S rRNA Gene Amplification Of Endophytic Bacteria Which Produces Antimicrobial Compounds - Rahmat Afif; Dwi Hilda Putri (Universitas Negeri Padang, 2019)
Cases of bacterial resistance to antibiotics are a serious problem in the world of health. Exploration to find new sources of antibiotics needs to be done, one of them is by utilizing endophytic bacteria Andaleh. The purpose of this study was to amplify the 16S rRNA coding gene, three isolates of Andaleh endophytic bacteria producing antimicrobial compounds with ATB A4.1, B.J.T.A.2.1, B.J.T.A.3 isolate code. This research is a descriptive research, carried out from November 2017 to June 2018 at the Research Laboratory of the Biology Department FMIPA UNP. The results showed that the amplification of the 16S rRNA gene from the three isolates succeeded in producing a single DNA band located between DNA bands 2027bp and 564 bp from the marker λ HindIII.